The Influence of Time Management, Academic Stress, Locus of Control Mediated by Family Support on Student Procrastination in Semarang City - Bayu Saputro; Qristin Violinda; Ira Setiawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aimed to assess the impact of time management, academic stress, and locus of control , mediated by family support, on student procrastination in Semarang. This study employed a quantitative methodology via a survey conducted among the student population in Semarang, employing random sampling to get a sample size of 399 respondents. The data were evaluated using validity assessments, discriminant validity, reliability evaluations, and hypothesis testing via Smart-PLS version 4.0. The test results indicated that time management, academic stress, locus of control , and family support significantly influenced procrastination. However, time management and academic stress did not exert a mediated effect through family support on procrastination. Additionally, academic stress was mediated by support for procrastination, while locus of control , mediated by family support, significantly affected procrastination. According to the test results, it is advisable for students to focus on time management and locus of control to mitigate procrastination tendencies. Families and universities offer enhanced support for emotional well-being and self-healing to assist students in managing academic stress.